(untitled) (Al-Mansour Journal, 2022)
In this paper the characteristics of a single-layer, dual-frequency antenna, which uses a stub-strip loaded rectangular microstrip patch, are studied. This antenna is easy to achieve good impedance matching at both resonance frequencies by setting the feed position or using other design parameters (tapered transmission lines). A detailed parameter study is performed and the theoretical analysis is based on the general transmission line theory. The effects of the various antenna parameters on two resonant frequencies, frequency ratio, bandwidth, and input impedance characteristics of the antenna are analyzed and discussed. It is shown that various frequency ratios (1.5–2.04) can be obtained by varying the length and width of the stub-strip loaded. A comparison between this work and other single layer dual-band techniques is made